Increased COX-2 Immunostaining in Urothelial Carcinoma of the Urinary Bladder Is Associated with Invasiveness and Poor Prognosis - Basim Al-Maghrabi; Wafaey Gomaa; Mohammed Abdelwahed; Jaudah Al-Maghrabi (Analytical Cellular Pathology)
Background. Urothelial carcinoma of the urinary bladder (UCB) is the commonest bladder tumor. Cyclooxygenase-2 (COX-2) mediates angiogenesis, cell survival/proliferation, and apoptosis. This study investigates the relation of COX-2 immunostaining in UCB to clinicopathological parameters in Saudi Arabia. Methods. The study population includes 123 UCB and 25 urothelial mucosae adjacent to UCB. UCB samples were collected before any local or systemic therapy. Tissue microarrays were designed and constructed, and TMA blocks were sliced for further immunohistochemical staining. Immunohistochemical staining was done using a mouse anti-human COX-2 monoclonal antibody. A cutoff point of 10% was chosen as the threshold to determine low and high COX-2 immunostaining. Results. COX-2 immunostaining is higher in UCB than in the adjacent urothelium (p=0.033). High COX-2 immunostaining is associated with high-grade UCB (p=0.013), distant metastasis (p=0.031), lymphovascular invasion (p=0.008), positive muscle invasion (p=0.017), pT2 and above (p=0.003), and high anatomical stages (stage II and above). High COX-2 immunostaining is an independent predictor of higher tumor grade (p<0.001), muscle invasion (p=0.015), advanced pathological T (p=0.014), lymphovascular invasion (p=0.011), and distant metastasis (p=0.039). High COX-2 immunostaining is associated with lower overall survival rate (p=0.019). Conclusion. COX-2 immunostaining is associated with the invasiveness of UCB which may be used as an independent prognostic marker. COX-2 may be a significant molecule in the initiation and progression of UCB. Molecular and clinical investigations are required to explore the molecular downstream of COX-2 in UCB and effectiveness of COX-2 inhibitors as adjuvant therapy along with traditional chemotherapy.